The Chinese electric vehicle industry's FDI in Hungary: A challenge for European policymakers - Louis Brennan; Viktor Eszterhai; Shaowei He (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
China's EV industry is investing heavily in Hungary giving it an additional mode of entry into the European market. As the EU attempts to protect European incumbent firms with the imposition of tariffs on EV imports from China, this investment creates a challenge for European policy makers.
Keywords: 330